Cover Feature: Palladium Complexes Based on Ylide‐Functionalized Phosphines (YPhos): Broadly Applicable High‐Performance Precatalysts for the Amination of Aryl Halides at Room Temperature (Chem. Eur. J. 19/2020). Issue 19 (1st April 2020) - Tappen, Jens; Rodstein, Ilja; McGuire, Katie; Großjohann, Angela; Löffler, Julian; Scherpf, Thorsten; Gessner, Viktoria H.
Abstract : Ylide‐substituted phosphines (YPhos) are excellent ligands for Pd‐catalyzed cross‐coupling reactions. This work examines the impact of different ligand substituents and the use of defined precatalysts on the catalyst activity in room temperature C−N couplings. Increased selectivities and activities are obtained with the backbone‐modified joYPhos ligand which exhibits extremely high activities (TOF>10 000 h −1 ) and productivities for the coupling of a variety of amines and aryl halides. More information can be found in the Full Paper by V. H. Gessner et al. on page 4281 .